An identification task toward engendering a Malaysian folktale classification system for preservation - Harun, Harryizman; Jamaludin, Zulikha (2016)
Malaysian folktales are one of the intangible cultural heritages that reflect and convey lineage of the past generations to the present. It deserves to be preserved systematically but thus far; such effort is scarce if not lacking in this country. Therefore, a study is conducted to engender a structural classification of the folktales with an aim to preserve such valuable heritage. However, before the classification begins, an important task precedes which are an identification of the Malaysian folktales in a form of literary sources. The identification task is guided by a combination of two qualifying factors: an operational definition established in the study and also an ownership of the folktales. Ultimately, this paper presents the method employed in the identification process and also the accepted and excluded Malaysian folktales as findings of the process.